A green, economical synthesis of β-ketonitriles and trifunctionalized building blocks from esters and lactones - Pienaar, Daniel P.; Butsi, Kamogelo R.; Rousseau, Amanda L.; Brady, Dean (Beilstein Journal of Organic Chemistry, 2019)
The acylation of the acetonitrile anion with lactones and esters in ethereal solvents was successfully exploited using inexpensive KOt-Bu to obtain a variety of β-ketonitriles and trifunctionalized building blocks, including useful O-unprotected diols. It was discovered that lactones react to produce the corresponding derivatized cyclic hemiketals. Furthermore, the addition of a catalytic amount of isopropanol, or 18-crown-6, was necessary to facilitate the reaction and to reduce side-product formation under ambient conditions.
Keywords: acylation; β-ketonitrile; enolizable; trifunctionalized; sustainable